Dendritic peptide bolaamphiphiles for siRNA delivery to primary adipocytes. (September 2018) - Eldredge, Alexander C.; Johnson, Mark E.; Cao, Yang; Zhang, Lin; Zhao, Can; Liu, Zhengxia; Yang, Qin; Guan, Zhibin
Abstract: Obesity is a major risk factor for diabetes, heart disease and other health problems. Adipose tissue plays a central role in the development of obesity and obesity-associated diseases. Gene therapy targeting adipose tissue may provide a promising strategy for obesity treatment. However, nucleic acid delivery to adipose tissue or even cultured adipocytes is challenging due to low delivery efficacy and high toxicity of the current cationic lipid based delivery systems, or monoamphiphiles. Herein, we report using dendritic peptide bolaamphiphiles (bolas) to deliver siRNA to primary adipocytes and hepatocytes. The bola consists of twol -Lysine dendrons connected to a fluorocarbon core through disulfide linkages. The Lysine dendrons are functionalized withl -histidine andl -tryptophan to promote endosomal escape and cellular uptake. The bola exhibited over 70% knockdown of GAPDH gene in both primary adipocytes and hepatocytes. Importantly, different from Lipofectamine that significantly reduced genes involved in lipolysis, lipogenesis, fatty acid oxidation and ketogenesis, the bolas had little to no effect on these genes. These results demonstrate the bola as a promising new vector for clinical and experimental applications for delivery of siRNA to metabolic organs.